Combined noninvasive ventilation and mechanical insufflator–exsufflator for acute respiratory failure in patients with neuromuscular disease: effectiveness and outcome predictors. (September 2019) - Chen, Tai-Heng; Liang, Wen-Chen; Chen, I-Chen; Liu, Yi-Ching; Hsu, Jong-Hau; Jong, Yuh-Jyh
Background: To determine the effectiveness of combined noninvasive ventilation (NIV) and mechanical insufflator-exsufflator (MI-E) for acute respiratory failure (ARF) in patients with neuromuscular disease (NMD), and outcome predictors. Methods: A prospectively observational study of patients with ARF was conducted in a pediatric intensive care unit (PICU). All received combined NIV/MI-E during PICU stays between 2007 and 2017. Pertinent clinical variables of heart rate (HR), respiratory rate (RR), pH, PaCO2, and PaO2 /FiO2 ratio were collected at baseline and at 2 h, 4-8 h, and 12-24 h after initiating use of NIV/MI-E. Treatment success was defined as avoiding intubation. Results: A total of 62 ARF episodes in 56 patients with NMD (median age, 13 years) were enrolled. The most frequent underlying NMD was spinal muscular atrophy (32/62, 52%). ARF was primarily due to pneumonia (65%). The treatment success rate was 86%. PICU stay and hospitalization were shorter in the success group (9.4 ± 6.1 vs. 21.9 ± 13.9 days and 16.3 ± 7.8 vs. 33.6 ± 17.9 days, respectively; both p  < 0.05). HR, RR, pH, and PaCO2 showed a progressive improvement, particularly after 4 h following successful NIV/MI-E treatment. RR decrease at 4 h, and pH increase and PaCO2 decrease at 4-8 h might predict success of NIV/MI-E treatment. The multivariate analysis identified PaCO2 at 4-8 h of 58.0 mmHg as an outcome predictor of NIV/MI-E treatment. Conclusions: Applying combined NIV/MI-E in the acute care setting is an efficient means of averting intubation in NMD patients with ARF. Clinical features within 8 h of the institution may predict treatment outcome. The reviews of this paper are available via the supplemental material section.